Home admission assessment in a Popular Council. - Silvia L. Pérez Groupierre; Irene E. Delgado Pérez; Alina Moreno Soca; Rubén Darío García Núñez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2003)
Background: The tendency in the present world is to develop ambulatory surgery, precocious discharge from hospital facilities, reduction of the number of beds in usage at the hospital and the increment of outpatients which bring about reduction in costs. Our health system incorporated the General Comprehensive doctor and nurse system in 1984 to the primary health assistance facilitating home admission. Objectives: To evaluate home admission in a popular council to determine the fulfillment and deficiency of such admission taking into account the diseases describe in the methodological folder in the new strategy held by the Public Health Minister. Methods: A descriptive study was carried out about the behavior of home admission. 178 patients belonging to 9 General Comprehensive doctor and nurse office in Aguada de Pasajero popular council in the last trimester were taken as sample of this study. Age, sex, causes of admission, average of staying, discharging state of the patient as well as evaluation of the clinical records and the follow up to the discharged patients were the variables analyzed. Results: Respiratory infections constituted the main cause of admission predominating the 15-59 year-old group with 53, 4% meanwhile 64, 2% belonged to female sex. Pregnancy affections were the highest causes of staying with 5, 3 days. 80 % of the families reported to be satisfied with this medical assistance modality.